Duplex camera portable motion capture system for single athlete’s performance analysis - Kaharuddin, Muhammad Zulhilmi (2020)
In recent years, introduction of depth camera in motion capture have caught a massive attention by both researchers and biomechanists. Therefore, high-performance sports certainly require motion capture technology to compete with other competitors. Thus, a study involving quantitative analysis is important to obtain a more accurate analysis. The purpose of this study is to develop duplex motion capture system for biomechanical analysis of sports. The visual sensor used in this research consists of two Kinect sensors Microsoft. The case studies were focused on a single athlete for sepak takraw pre-serve and bunga silat at any single time. MATLAB and Software Development Kit (SDK) by Microsoft were used as software developing platform. Accuracy between software developed in MATLAB platform and SDK were compared and the best platform in term of performance and accuracy were chosen. “Bunga silat” in Silat and sepak takraw pre-serve were chosen as the case studies to justify the feasibility of the system. This study also examined the capability of Kinect Xbox 360° sensor and software to be used in biomechanical analysis. Result obtained revealed significant achievement in terms of motion capture system in the biomechanical analysis on certain sports. For Sepak Takraw, the foot-to-foot distance and angle of knee before serve has been used as a parameter to determine the speed of the ball to be serviced. In this research the highest ball speed recorded is 69km/h with 1.0664m of foot-to-foot distance and 147.20° of right knee 153.52° for the left knee at the pre-serve phase. Whereas for Silat, it shows that the amateur motion is very much similar from the practitioners. The closer the mean and standard deviation value to unity the more accurate the movement referred to the benchmark stated. Therefore, to increase the accuracy of movement execution, the subject needs to repeat the movement execution until perfection which is set by the teacher. In summary, this research successfully described an athlete’s performance quantitatively using motion capture system.